Chas. Ben. Darwin, Ordinances of the City of Burlington, with Head Notes and an Analytic Index (1856) 159, § 9 - (:unkn) unknown (General Publisher, 1856)
Empowered the mayor, wharf master, and the fire wardens to give direction to boats containing gun powder, gun cotton, hay, or other combustible materials.
--
Keywords: GUN POWDER TRANSPORTATION